DMD-based hyperspectral microscopy with flexible multiline parallel scanning - Dong, Xue; Tong, Geng; Song, Xuankun; Xiao, Xingchen; Yu, Yiting (Microsystems & nanoengineering, 2021)
As one of the most common hyperspectral microscopy (HSM) techniques, line-scanning HSM is currently utilized in many fields. However, its scanning efficiency is still considered to be inadequate since many biological and chemical processes occur too rapidly to be captured. Accordingly, in this work, a digital micromirror device (DMD) based on microelectromechanical systems (MEMS) is utilized to demonstrate a flexible multiline scanning HSM system. To the best of our knowledge, this is the first line-scanning HSM system in which the number of scanning lines N can be tuned by simply changing the DMD’s parallel scanning units according to diverse applications. This brilliant strategy of effortless adjustability relies only on on-chip scanning methods and totally exploits the benefits of parallelization, aiming to achieve nearly an N -time improvement in the detection efficiency and an N -time decrease in the scanning time and data volume compared with the single-line method under the same operating conditions. To validate this, we selected a few samples of different spectral wavebands to perform reflection imaging, transmission imaging, and fluorescence imaging with varying numbers of scanning lines. The results show the great potential of our DMD-based HSM system for the rapid development of cellular biology, material analysis, and so on. In addition, its on-chip scanning process eliminates the inherent microscopic architecture, making the whole system compact, lightweight, portable, and not subject to site constraints.